2006
DOI: 10.1136/hrt.2005.083204
|View full text |Cite
|
Sign up to set email alerts
|

The logistic EuroSCORE in cardiac surgery: how well does it predict operative risk?

Abstract: The logistic EuroSCORE is a reasonable overall predictor for contemporary cardiac surgery but overestimates observed mortality. Its accuracy at predicting risk in different surgical subgroups varies. The logistic EuroSCORE should be recalibrated before it is used to gain reassurance about outcomes. Caution should be exercised when using it to compare hospitals or surgeons with a different operative case mix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
73
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(86 citation statements)
references
References 14 publications
9
73
1
2
Order By: Relevance
“…Multiple reports from different countries have demonstrated the EuroSCORE to significantly overestimate operative mortality for AVR [10][11][12][13]. With this study, we confirm that the EuroSCORE overestimates operative mortality for AVR in the Dutch population as well.…”
Section: Survival Estimatessupporting
confidence: 83%
“…Multiple reports from different countries have demonstrated the EuroSCORE to significantly overestimate operative mortality for AVR [10][11][12][13]. With this study, we confirm that the EuroSCORE overestimates operative mortality for AVR in the Dutch population as well.…”
Section: Survival Estimatessupporting
confidence: 83%
“…20,21 Patients were evaluated by a team of calibrated dentists who determined oral health status and specific dental treatment needs before surgery. The patients were then enrolled in a protocol for oral decontamination, which consisted of instructing the patient on oral hygiene using the modified Bass technique.…”
Section: Methodsmentioning
confidence: 99%
“…These results are in keeping with recent evidence which suggests that the logistic EuroSCORE over estimates mortality, and requires recalibration. 25 The SYNTAX trial has also shown that early outcomes after PCI are related to initial lesion characteristics, however new evidence also suggests that these early outcomes after PCI can be influenced by adverse patient characteristics as assessed by the EuroSCORE. 26,27 Clearly, the late outcomes after PCI are determined by the need for repeat revascularisation.…”
mentioning
confidence: 99%